VOC ship Batavia a virtual voyage of a 17th century ship - Berge, Peter van den; Bart Van der Mei; APAC Media ([S.l.] : APAC Media)
Provides information about historical background of the Batavia, building of Batavia and also interactive tour
System requirements: Pentium 1-166 MHz, 32 MB RAM; sound blaster compatible sound card; 4MB VGA (1,000 colour) video card; 20 speed (CD-ROM)
Keywords: Batavia (ship); Ships -- Reconstruction; Shipbuilding -- History; Ships -- History; Shipyards